Methodological issues in management research : advances, challenges and the way ahead - Subudhi, Rabi N.; Mishra, Sumita (Emerald Publishing Limited, 2019)
Using contemporary examples of business and management research, predominantly within the context of India, this book offers numerous tools and techniques which can be applied to a diverse range of needs in social science research. With contributions from subject-experts in the field of research methodology and teachers of research methodology courses in leading business schools and universities of India, the book covers the essentials of management research. Covering both qualitative and quantitative research, topics discussed include: literature reviews research designs qualitative and quantitative data analysis grounded theory research questionnaires, focus groups, and interviews hypothesis testing case study research emerging trends in research and some advanced analysis. Specially selected Research Cases provide examples of some typical management research topics, outlining the detailed stages of their respective research processes and the latest data analysis techniques using SPSS, AMOS and STRATA. This practical element emphasises the variety of research methods and when/how to use them, making this book a useful resource for researchers from various academic disciplines and professional backgrounds.
Foreword / Rajendra Nargundkar -- Chapter 1. Introduction: the methodological domain in management research / Sumita Mishra and Rabi N. Subudhi -- Chapter 2. Review of literature / Sumita Mishra -- Chapter 3. Purpose and process of research / Shikta Singh -- Chapter 4. Research design / Fakir M. Sahoo -- Chapter 5. Questionnaire design / Sudhakar Patra -- Chapter 6. Qualitative interviewing / Upasnaa Agarwal -- Chapter 7. Focus group discussions / Vijayalakshmi C. Balasubramaniam -- Chapter 8. Quantitative data analysis / Punyaslok Dhall -- Chapter 9. Testing of hypothesis: concepts and applications / Rabi N. Subudhi -- Chapter 10. Nature of qualitative research / Richa Awasthy -- Chapter 11. Case study research / Srilata Patnaik and Satyendra C. Pandey -- Chapter 12. Grounded theory: a method of research inquiry / Sunil Sharma, Atri Sengupta and Subhash Chandra Panja -- Chapter 13. DEA, structural modelling and non-parametric tests / PKJ Mohapatra -- Chapter 14. Special section on sample research papers -- Chapter 14.1. Working with second order construct in measurement model: an illustration using empirical data / Subhra Pattnaik -- Chapter 14.2. Role of self-congruity in predicting travel intention / Joydeep Biswas and Shabbirhusain RV -- Chapter 14.3. Structural equation modelling: threshold criteria for assessing model fit / Malabika Sahoo -- Chapter 14.4. Socio-Economic development disparity in India: an inter-state analysis / Ayushi Raichoudhury -- Chapter 14.5. Stages and methods for cleaning large secondary data using R / Manoj K. Jena & Brajaballav Kar -- Appendix -- Statistical Tables.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Management -- Research -- India; Management -- Research -- Methodology; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management